So x4 - 1 is the difference of squares, so x4 - 1 = (x2 - 1)(x2 + 1) = (x + 1)(x - 1)(x2 + 1).
Chat with our AI personalities
which of the following is a factor of x2 - 5x - 6
7(x - 2)(x + 2)
Two to the fourth power times 5 to the fourth power equals 10,000
This is like a² - b², with a = 9x² and b = 9y². This can be factored as (a - b)(a + b), then substitute for a & b: (9x² - 9y²)(9x² + 9y²), then (9x² - 9y²) can factor to (3x - 3y)(3x + 3y) so we have: (3x - 3y)(3x + 3y)(9x² + 9y²)
0.6 to the fourth power equals 0.1296